2002
DOI: 10.1080/pdp.21.1.31.39
|View full text |Cite
|
Sign up to set email alerts
|

T and B Cell Repertoire in Gastric Lymph Follicles in Children With Helicobacter Pylori Infection

Abstract: Helicobacter pylori infection has been implicated in the development of gastrointestinal malignancy in adults and children. The histopathological processes that lead to such development are unknown. We compared the immune cell repertoire of mucosal lymph follicles in children with H. pylori infection to B cell type mucosal associated lymphoid tissue (MALT)-lymphoma of adults. The B and T cell populations residing within the lymph follicles and/or within B cell type MALT lymphoma were characteriZed by an immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Moreover, our results demonstrated that lymphocytes in the lymph follicles were CD20-positive B cells, which is consistent with the results of previous studies [34,35]. Although hepcidin mRNA is known to be expressed in both T cells and B cells, our results support the idea that B cells infiltrating the mucosa play a major role in the production of hepcidin in the H. pylori-infected gastric mucosa.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, our results demonstrated that lymphocytes in the lymph follicles were CD20-positive B cells, which is consistent with the results of previous studies [34,35]. Although hepcidin mRNA is known to be expressed in both T cells and B cells, our results support the idea that B cells infiltrating the mucosa play a major role in the production of hepcidin in the H. pylori-infected gastric mucosa.…”
Section: Discussionsupporting
confidence: 93%